Zarządzanie strategiczne muzeum martyrologicznym i miejscem pamięci na przykładzie Państwowego Muzeum Auschwitz-Birkenau w Oświęcimiu - Praga, Agnieszka (Załącznik Kulturoznawczy, 2023)
Auschwitz-Birkenau State Museum, located on the territory of the former Nazi’s concentration camp, is an example of what a French historian, Pierre Nora, called ‘a site of memory’ (lieu de mémoire) – a place which serves to commemorate and symbolize the biggest genocide and the tragedy of the twentieth century, that is the Holocaust. Hence, the management of the institution like this has to include both market-based as well as ethical factors. Moreover, since the Museum uses many elements of the original concentration camp’s infrastructure, the question arises whether it should aim to preserve the authenticity of this place, or rather follow the main trends in the museology (digitalization, wide multimedia environment etc.). The authoress analyzes the management strategy of the Museum by taking into account the statistical data, its educational offer, as well as the currently realized projects and programs